Geochemical and Os-Hf-Nd-Sr isotopic characterization of north patagonian mantle xenoliths: Implications for extensive melt extraction and percolation processes - Mundl, A. (2016)
Alkali basalt hosted mantle xenoliths were sampled at four locations within the North Patagonian Massif, Argentina. The subcontinental lithospheric mantle (SCLM) beneath Comallo, Puesto Diaz and Cerro Chenque is mostly represented by spinel-harzburgites, whereas at Prahuaniyeu, spinel-garnet- and garnet-peridotites occur next to spinel-peridotites. Partial melting estimates for the north Patagonian mantle xenoliths determined from clinopyroxene trace element abundances reveal up to 25% melt extraction. Whereas the SCLM beneath Puesto Diaz, Cerro Chenque and Comallo is exclusively represented by highly depleted mantle xenoliths, the Prahuaniyeu sample suite comprises both fertile lherzolites and depleted harzburgites. Elevated trace element contents in all the studied north Patagonian mantle samples indicate that melt-rock interaction took place after an initial melt depletion event. Variable primitive mantle normalized REE patterns of clinopyroxenes from within one sample locality suggest compositional changes attributed to melt percolation, which has not significantly affected the bulk-rock and mineral major element compositions. Melt percolation processes have also been detected in the isotopic compositions of the xenoliths, as well as in their highly siderophile element systematics. Hf isotopic compositions are decoupled from those of Nd and Sr and have been affected by variable degrees of enrichment. Platinum group element (PGE) abundances also reveal indications of melt-rock reaction. In some samples this is reflected in fractionation of the iridium-group PGE and/or enrichment in the palladium-group PGE and/or rhenium, which cannot result merely from partial melting processes. Rhenium depletion ages (TRD) determined from Os isotopic analyses reveal an at least late Paleoproterozoic (1·7 Ga) stabilization of the Prahuaniyeu SCLM. Mantle xenoliths sampled from beneath Comallo and Puesto Diaz-Cerro Chenque yield distinctly younger TRD of 1·3 Ga and 1·0 Ga, respectively. Distinct differences in the character of mantle xenoliths from Prahuaniyeu and from Puesto Diaz and Cerro Chenque (i.e. SCLM stabilization age and range of fertility) suggest that at least two SCLM domains exist below the North Patagonian Massif.